The governance mechanism of professional sports - Zheng, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: After more than 100 years of development, professional sports have become a mature industry that yields a tremendous impact. This is in stark contrast to the difficulties faced by the development of professional sports. Through the studies of professional sports, this paper aims to reveal the underlying laws of professional sports development and provide useful lessons for the development of China`s professional sports. Methods A comprehensive literature review to establish background information was conducted. Case study analysis also took place. Discussion This paper conducted a systematic analysis of the organizational structure and institutional arrangements specific to professional sports from the perspective of contract governance with the core concept being "asset specificity". Second, the paper analyzes the history of professional sports using case studies and the contract governance theory. Leagues and clubs, including two of the main professional sports with organizational structure were considered. Finally, based on the layered theory, the author proposes some organization and institution reform strategies. Conclusions Specific investment of the main players in the professional sports market determines the transaction dimensionality and the contract process that organization and institutions interact with in forming layered contract governance mechanisms. Professional sports organizations and institutions were formed by market stakeholders to prevent opportunism and protect specific investment. Organization and institutions influenced each other as specific investment changed. The overall trend is from simple to complex, from rudimentary to sophisticated, displaying a layered evolution pattern. Professional sports market stakeholders all undertake high levels of specific investment. The crucial problem in China`s professional market is the mismatch between specific investment and profit control. Currently there are no organizations and institutions to protect stakeholders` specific investment which leads to widespread opportunism.